2011
DOI: 10.1007/s15010-011-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of occult Hepatitis B infection in HIV-1 infected individuals during highly active antiretroviral treatment interruption and after HAART resumption

Abstract: The intermittent nature of HBV-DNAemia poses a diagnostic challenge, but no association was found with transaminase levels at any time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The clinical significance of occult HBV infection in HIV‐infected patients is still controversial . Therefore, we evaluated whether occult HBV infection contributes to liver damage in HIV‐infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of occult HBV infection in HIV‐infected patients is still controversial . Therefore, we evaluated whether occult HBV infection contributes to liver damage in HIV‐infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the available data suggest seronegative patients have a different clinical evolution and should therefore be evaluated separately. Another factor that is common in HIV patients and that is known to affect [46] Iran 3 (13.6) 2 (9.1) ND 1 (4.5) Bagaglio et al [47] Italy 9 (31.0) 9 (31.0) ND ND Bell et al [48] Africa [51] Spain 6 (2.4) 2 (0.8) 4 (1.6) ND Filippini et al [13] Italy 17 (20.0) 11 (12.8) 3 (3.5) 3 (3.5) Firnhaber et al [23] Africa 38 (88.4) 38 (88.4) ND ND Gupta et al [30] India 24 (45.3) 13 (24.5) 11 (20.8) ND Hakeem et al [52] Scotland 2 (2.8) 2( 2.9) ND ND Jardim et al [19] Brazil 8 (5.0) 2 (1.3) 6 (3.8) ND Khamduang et al [35] Thailand 47 (23.5) 47 (23.5) ND ND Liang et al [53] Taiwan 3 (2.3) 3 (2.3) ND ND Lo Re et al [54] United States 17 (10.0) 10 (5.6) 7 (3.9) ND Loustaud-Ratti et al [55] France [24] Africa 51 (10.0) 51 (11.8) ND ND Neau et al [58] France 1 (0.6) 1 (0.6) ND ND Nebbia et al [59] England 48 (14.0) 48 (14.0) ND ND Opaleye et al [25] Nigeria 21 (11.2) 8 (4.3) 9 (4.8) 2 (1.1) Panigrahi et al [26] India 12 (10.7) 9 (8.0) 3 (2.7) ND Santos et al [20] Brazil 16 (15.8) 2 4 (4.0) 12 (11.9) ND Sen et al [27] India 1 (5.6) 2 1 (5.6) ND ND Shire et al [60] United States 4 (10.5) 4 (10.5) ND ND Shire et al [61] United States 12 (30.2) 3 (7.0) 5 1 (11.6) 5 (11.6) Sucupira et al [21] Brazil 6 (18.8) 2 3 (9.4) 3 (9.4) ND Torres Barranda et al [22] Mexico 7 (18.4) 1 (2.6) 1 (2.6) 5 (13.2) Tramuto et al [62] Italy 24 (5.9) 8 (2.0) 7 1 (1.7) 9 (2.2) Tsui et al [63] United States 8 (2.0) 8 (2.0) ND ND 1 In some studies the anti-HBsAg positive group was also included; 2 Prevalence calculated using the reported data; anti-HBsAg+, antibodies against hepatitis B surface antigen positive; anti-HBcAg+ antibodies against hepatitis B core antigen positive. Prevalence (%) were included for each group of patients studied according the HBV serological markers (Anti-HBsAg-/anti-HBcAg+, Anti-HBsAg+/anti-HBcAg+, Anti-HBsAg-/anti-HBcAg-).…”
Section: Clinical Significancementioning
confidence: 99%
“…Among the 29 HIV-infected individuals positive for anti-HBc and negative for HBsAg included in the study, nine (31%) showed signs of overt HBV infection during the 100-week study period: three patients showed intermittent serum HBV DNA, while six patients were HBV DNA-positive only at 16 weeks following HAART resumption. The HBV DNA load invariably fell below the sensitivity of the quantitative test after the resumption of ART [15].…”
Section: Discussionmentioning
confidence: 95%
“…The role of the immune system in controlling HBV replication has also been highlighted in a recent study where the potential effect of the interruption and subsequent re-introduction of highly active antiretroviral therapy (HAART) on the frequency and dynamics of overt HBV infection in HIV-infected individuals was investigated [15]. Among the 29 HIV-infected individuals positive for anti-HBc and negative for HBsAg included in the study, nine (31%) showed signs of overt HBV infection during the 100-week study period: three patients showed intermittent serum HBV DNA, while six patients were HBV DNA-positive only at 16 weeks following HAART resumption.…”
Section: Discussionmentioning
confidence: 99%